Determinação das propriedades mecânicas da liga A356 conformada por spray para diferentes teores de ferro e condições de processamento - Silva Junior, Altino Ribeiro da (Universidade Federal de São Carlos, 2008)
The aims of this work were the microstructural and tensile properties characterization of the hypoeutectic spray formed Al-Si 356, with and without contamination for iron, spray formed, extruded and heat treatment. The alloys were melted by induction furnace, gas atomized with nitrogen and deposited onto a copper substrate, after that the deposits had been parted and hot extrusion. Later some samples had been submitted the heat treatments. Spray formed material showed fine and homogenous microstructure, composed by equiaxial _-Al matrix, silicon particles and _-AlFeSi intermetallics phases, for contaminated samples. Higher porosity and lower yield process were obtained increasing the superheating temperature. The extrusion promoted grain refinement by a recrystallization process and strong decrease of the porosity. Room temperature tensile tests of the spray formed Al-Si 356 alloy showed both increased tensile strength and elongation when compared with the values observed for conventionally cast counterparts. These results can be ascribed to the refined grain size, silicon particles morphology and smaller _- AlFeSi phases presented in spray formed deposits. When, the samples spray formed and extruded showed higher values for the ultimate tensile strength and ductility when compared to Al-Si 356 alloy deposits processed by same parameters. The heat treatment samples of the Al- Si contaminated with iron, showed higher values for the tensile strength and lower decrease for the elongation when compared to spray formed and extruded.
Determination of the mechanical properties of spray formed A356 alloy for different contents of iron and conditions of processing
Keywords: Metais; Conformação por spray; Ligas de alumínio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA